2020
DOI: 10.1177/2050313x20945531
|View full text |Cite
|
Sign up to set email alerts
|

Severe chronic bowel obstruction associated with brown bowel syndrome

Abstract: A 61-year-old alcoholic male with history of cholecystectomy presented with a 20-year history of recurrent bowel obstruction and a 30 lb weight loss. After numerous attempts at conservative management, exploratory laparotomy was performed, which showed no mechanical cause. Despite no clear etiology, the obstruction persisted and intensified. A follow-up computed tomography scan revealed a small bowel obstruction with concurrent megacolon. A total abdominal colectomy was performed, with ileostomy. Grossly, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Nutritional status should be evaluated and enteral or parenteral nutrition with vitamin substitution should be accordingly provided. Some authors reported clinical and histological improvement with regression of lipofuscin aggregates after underlying disease treatment and vitamin E substitution [ 13 , 14 , 15 ]. Moreover, vitamin E supplementation could prevent further lipofuscin accumulation and thus further deterioration of the clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status should be evaluated and enteral or parenteral nutrition with vitamin substitution should be accordingly provided. Some authors reported clinical and histological improvement with regression of lipofuscin aggregates after underlying disease treatment and vitamin E substitution [ 13 , 14 , 15 ]. Moreover, vitamin E supplementation could prevent further lipofuscin accumulation and thus further deterioration of the clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Full-thickness rectal biopsy excluded adult Hirschsprung's disease and the deposition of lipofusin-like pigments observed throughout the bowel wall into the deeper muscularis propria excluded melanosis coli, which is usually confined to the mucosa. [6][7][8] In patients presenting with suspected BBS, work up includes a thorough clinical history for risk factors, followed by serological parameters (e.g. C-reactive protein, albumin, total protein, transglutaminase immunoglobulin A and so on) and serum levels of fatsoluble vitamins for the diagnosis of malabsorptive disorders.…”
Section: Brown Bowel Syndrome: a Rare Cause Of Intestinal Obstructionmentioning
confidence: 99%